2022
DOI: 10.1007/s10533-022-00915-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing carbon and nitrogen microbial assimilation in suspended particles in freshwaters

Abstract: The dynamic interactions between dissolved organic matter (DOM) and particulate organic matter (POM) are central in nutrient cycling in freshwater ecosystems. However, the molecular-level mechanisms of such interactions are still poorly defined. Here, we study spatial differences in the chemical (i.e., individual proteinaceous amino acids) and microbial (i.e., 16S rRNA) composition of suspended sediments in the River Chew, UK. We then applied a compound-specific stable isotope probing (SIP) approach to test th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Such elevated nutrient concentrations are commonly observed in UK agricultural catchments (Yates et al 2019a). Contradictory observations from Graeber et al (2012) and others (Sachse et al 2005) suggest catchments with a high proportion of agricultural activity export structurally complex DOM, characterised by elevated DOC concentrations and a dominance of humic-like fluorescent DOM, though other studies (Lloyd et al 2021;Mena-Rivera et al 2021) indicate DOM in agricultural catchments has a high proportion of lower molecular weight compounds resulting from microbial processing of terrestrially derived DOM. Similarly, both Yates et al (2019a) and Williamson et al (2021) in a pan-UK study concluded that higher DOC, higher Specific UV Absorbance (SUVA) and higher DOC:DOC ratios were consistently observed in peaty catchments than in lowland intensively farmed agricultural catchments.…”
Section: Introductionmentioning
confidence: 98%
“…Such elevated nutrient concentrations are commonly observed in UK agricultural catchments (Yates et al 2019a). Contradictory observations from Graeber et al (2012) and others (Sachse et al 2005) suggest catchments with a high proportion of agricultural activity export structurally complex DOM, characterised by elevated DOC concentrations and a dominance of humic-like fluorescent DOM, though other studies (Lloyd et al 2021;Mena-Rivera et al 2021) indicate DOM in agricultural catchments has a high proportion of lower molecular weight compounds resulting from microbial processing of terrestrially derived DOM. Similarly, both Yates et al (2019a) and Williamson et al (2021) in a pan-UK study concluded that higher DOC, higher Specific UV Absorbance (SUVA) and higher DOC:DOC ratios were consistently observed in peaty catchments than in lowland intensively farmed agricultural catchments.…”
Section: Introductionmentioning
confidence: 98%
“…Microbial nitrogen assimilation primarily occurs via the conversion of nitrate into ammonia by a series of enzymes such as nitrate reductase and nitrite reductase ( Matassa et al, 2016 ). These microorganisms then use this ammonia for amino acid synthesis and transformation ( Mena-Rivera et al, 2023 ). Amino acids are primarily used to synthesize proteins that can then be modified, sorted, transported, and stored in microbial organisms ( Xu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The approach combines compound-specific gas chromatography–combustion-isotope ratio mass spectrometry (GC–C-IRMS) and 15 N-SIP in the meta-metabolome of the whole soil system (Knowles et al 2010 ; or other complex media, e.g. river water; Mena-Rivera et al 2022 ) and is essentially a targeted 15 N fluxomics approach (Cascante and Marin 2008 ). The soil protein pool is the largest (20%–50% of total soil N), and arguably most important, identifiable class of soil organic N (Stevenson 1982 ).…”
Section: Introductionmentioning
confidence: 99%